Tocqueville's political economy - Swedberg, Richard (Princeton University Press, 2009)
"In Tocqueville's Political Economy, Richard Swedburg shows that Alexis de Tocqueville had a highly original and suggestive approach to economics - one that still has much to teach us today." "Through careful readings of Tocqueville's two major books and many of his other writings, Swedburg lays bare Tocqueville's ingenious way of thinking about major economic phenomena. When examined together, Swedburg argues, these books and other writings constitute an interesting alternative model of economic thinking, as well as a major contribution to political economy that deserves a place in contemporary discussions about the social effects of economics"--Jacket